Evaluating Risk and Possible Adaptations to Climate Change Under a Socio-Ecological System Approach - Haro, Abi; Mendoza-Ponce, Alma; Calderón-Bustamante, Óscar; Velasco, Julián A.; Estrada, Francisco (Frontiers in Climate, 2021)
Evidence suggests that climate change could drastically reduce Mexico's agricultural productivity with severe socio-ecological consequences. Population growth and the increasing demand of resources will exacerbate these impacts. Focusing on rainfed maize production, we evaluate the socio-ecological risk that municipalities currently face and how climate change could modify it. Municipalities were classified based on their biophysical and socioeconomic traits like temperature, precipitation, population, gross domestic product, marginalization, and agricultural subsidies. The study identifies municipalities that would face higher risk under climate change conditions, and it evaluates whether increases in agricultural subsidies could be effective for reducing the farmers’ future risk. Our results show that during the 2010s, 36.8% of the municipalities and 15% of the population were at very high and high risk, respectively. By 2070, under a high-warming scenario these figures increase to 56.5% and 18.5%. We find that a generalized augment in agricultural subsidies is not enough to compensate for the effects of climate change on the socio-ecological risk of rainfed maize producers. We suggest that transformative adaptation is required for managing the agricultural risk that socio-ecological systems experience under climate change conditions. Such adaptation strategies should include poverty alleviation, promotion of resistant and native varieties of crops, capacity building to improve management and water use, sustainable technification, and soil restoration.